The Costa Rican Systenus Loew (Diptera: Dolichopodidae): rich local sympatry in an otherwise rare genus - Bickel, Daniel J. (Zootaxa, 2015)
The Costa Rican Systenus Loew (Diptera: Dolichopodidae: Medeterinae) are described, illustrated and keyed, and comprise nine new species: Systenus divericatus sp. nov., S. eboritibia sp. nov., S. emusorum sp. nov., S. flavifemoratus sp. nov., S. maculipennis sp. nov., S. naranjensis sp. nov., S. parkeri sp. nov., S. tenorio sp. nov., and S. zurqui sp. nov. Eight species are known only from Malaise traps at a locale in Guanacaste Province, in contrast to a single species collected as part of the long running INBio survey of the Costa Rican insect fauna. On a global scale, Systenus is uncommon in collections, possibly the result of its known larval tree hole habitat and adult arboreal associations, making the genus less likely to be captured by ground-level trapping. This makes the high level of sympatry at one site even more remarkable and suggesting that more cryptic species-rich arboreal faunas await discovery.